Ten Long Years - Alan Bettersby (UK Cambridge University Press, 2013)
New York private investigator Nat Marley meets a stranger who is celebrating his release from prison after a ten-year sentence. The man wants to trace an old friend and reclaim the money which the friend is holding for him. Finding the 'friend' turns out to be relatively easy, but getting hold of the money is quite another matter.